Influence of moisture content in some mechanical properties of two brazilian tropical wood species - Branco, L. A. M. N.; Chaud, Eduardo; Christoforo, André L.; Lahr, Francisco Antonio Rocco; Battistelle, Rosane Aparecida Gomes [UNESP]; Valarelli, Ivaldo De Domenico (Trans Tech Publications, 2014)
This study aimed, with the aid of analysis of variance (ANOVA), to investigate and quantify the influence of moisture ranging between 12% and over 30% (fiber saturation) on the mechanical properties: strength and modulus of elasticity in compression and in tension parallel to grain; modulus of rupture and modulus of elasticity in static bending; shear strength parallel to grain considering wood species Ipê (Tabebuia sp) and Angelim Araroba (Vataireopsis araroba). Tests were performed according to the assumptions and calculating methods Brazilian standard ABNT NBR 7190, Anexx B, totalizing 400 tests. Results of ANOVA revealed a significant reduction (16% on average) for mechanical properties wood due to the increase in moisture content from 12% to over 30% (fiber saturation). The same behavior also occurred when assembly containing the two species was considered.
Keywords: Moisture content; Tropical Brazilian wood species; Wood properties